Resonance assignments of the myristoylated Y28F/Y67F mutant of the Mason-Pfizer monkey virus matrix protein - Doležal, Michal; Hrabal, Richard; Ruml, Tomáš; Rumlová, Michaela (Biomolecular NMR assignments, 2015)
The matrix protein (MA) of the Mason-Pfizer monkey virus (M-PMV) plays a key role in the transport and budding of immature retroviral particles from the host cell. Natural N-terminal myristoylation of MA is essential for the targeting of the particles to the plasma membrane and participates in the interaction of MA with membranes phospholipids. The mutation Y28F/Y67F in MA reduces budding and thus causes the accumulation of viral particles under the cytoplasmic membrane. To investigate the impact of Y28F/Y67F mutation on the structure of MA, we prepared this protein in amount and quality suitable for NMR spectroscopy. We report backbone, side-chain and myristoyl residue assignments of the Y28F/Y67F mutant of the M-PMV matrix protein, which will be used to study the interaction with membrane phospholipids and to determine the structure of the mutant matrix protein.
Keywords: Proton Magnetic Resonance Spectroscopy; Viral Matrix Proteins; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Mutant Proteins; Myristic Acid; Nuclear Magnetic Resonance, Biomolecular; Protein Structure, Secondary; nukleární magnetická rezonance biomolekulární; Mason-Pfizer monkey virus; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; kyselina myristová; Masonův-Pfizerův opičí virus; protonová magnetická rezonanční spektroskopie; proteiny virové matrix; mutantní proteiny; sekundární struktura proteinů